Surgical treatment of hemorrhoids: a critical appraisal of the current options - CERATO,Marlise Mello (2014)
Introduction : Surgical treatment of hemorrhoids is still a dilemma. New techniques have been developed leading to a lower rate of postoperative pain; however, they are associated with a greater likelihood of recurrence. Aim : To review current indications as well as the results and complications of the main techniques currently used in the surgical treatment of hemorrhoidal disease. Methods : A systematic search of the published data on the options for treatment of hemorrhoids up to December 2012 was conducted using Medline/PubMed, Cochrane, and UpToDate. Results : Currently available surgical treatment options include procedure for prolapse and hemorrhoids (PPH), transanal hemorrhoidal dearterialization (THD), and conventional hemorrhoidectomy techniques. Excisional techniques showed similar results regarding pain, time to return to normal activities, and complication rates. PPH and THD were associated with less postoperative pain and lower complication rates; however, both had higher postoperative recurrence rates. Conclusion : Conventional surgical techniques yield better long-term results. Despite good results in the immediate postoperative period, PPH and THD have not shown consistent long-term favorable results.